Validation of four names of Castanopsis (Fagaceae) from Hainan, Southern China (Bangladesh Journal of Plant Taxonomy, 2011)
Not availableKeywords: Castanopsis; China; Fagaceae; Hainan; Nomenclature; Validation. DOI: 10.3329/bjpt.v18i1.7843Bangladesh J. Plant Taxon. 18(1): 77-79, 2011 (June)